Beyond Pandora: the human and civic female body (5th – 4th centuries BC) - Alexandre Aniceto, Bárbara (Romanitas - Revista de Estudos Grecolatinos, 2023)
From Classical Antiquity to our days, cultural markers of gender crossed and still cross the understanding of the body. They give meaning to the identities deemed feminine and masculine in a historical context. In Classical Greek societies, such markers draw on, to a greater or lesser extent, “the race of women”, a category set apart from humanity since it was founded on the mythical figure of Pandora. However, the textual testimonies of the period, notably Aristophanic comedy and Hippocratic medicine, reveal to us that such mythical canon did not limit the possibilities of representation and the uses of female bodies, especially concerning married women. Thus, this article aims to show that both Aristophanes and Hippocrates express a masculine thought capable of including the feminine as an active participant in the construction of the human body and the Athenian civic body.